THE EFFECT OF SUSTAINABILITY REPORT DISCLOSURE ON COMPANY VALUE WITH SYSTEMATIC RISK AS A MEDIATION VARIABLE - Anthony Holly; Robert Jao; Ana Mardiana; Anita Holly (Universitas Katolik Indonesia Atma Jaya, 2022)
This research is aimed to investigate the impact of sustainability report to firm value with systematic risk as mediating variable. Sample of this research are companies listed in Indonesia Stock Exchange (IDX) as sample in 2016-2018. Sample selected by purposive sampling method gathered from companies which disclose their financial report and sustainability report in a row, taht gathered 3 years periode are 63 sample. Using path analysis as reseach method. The study results show sustainability report has negative and significant effect to systematic risk. Sustainability report has negative and no significant effect to firm value and systematic risk mediates the effect of sustainability report to firm value.